Development of Teaching Materials with a Socio-Scientific Issues Context on the Nuclear Power Plant Theme - Moh. Taufiq Juhandi; Asep Saefullah; Firman Septiyanto (JURNAL PEMBELAJARAN FISIKA, 2025)
Indonesia plans to construct Nuclear Power Plants (NPPs) to meet energy demands and align with the government’s commitment to Net Zero Emission (NZE). However, this development faces numerous challenges, including public resistance. Most of this opposition stems from concerns and negative stigma surrounding nuclear energy, exacerbated by the public's limited knowledge, including students, about nuclear energy and its application in NPPs. Therefore, the development of teaching materials with a Socio-Scientific Issues (SSI) context on the theme of NPPs will be undertaken. The purpose of this research is to determine the feasibility of SSI-based teaching materials on the theme of NPPs to facilitate students' critical thinking skills. This study adopts a Research and Development (RnD) model, with the development of teaching materials following the ADDIE model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. In this study, the procedure is limited to the development stage. The validation results for the content achieved a score of 77.81% in the "feasible" category, while the media validation scored 79.16%, also in the "feasible" category. The results of the student response questionnaire showed an average score of 74.33%, classified as "interesting". Based on these results, the developed teaching materials are categorized as “feasible” and suitable for use in 12th-grade high school physics learning.